2013
DOI: 10.1016/j.techfore.2012.07.011
|View full text |Cite
|
Sign up to set email alerts
|

How the internet of things technology enhances emergency response operations

Abstract: Abstract-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
146
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(162 citation statements)
references
References 46 publications
(48 reference statements)
1
146
0
2
Order By: Relevance
“…For many decades, Situation Awareness (SA) has been identified as one of the critical concepts to be considered (Yang et al, 2013). In this research Yang et al (2013) concluded that firefighters fear using technology as they are worried about the reliability of the existing systems and have procrastinated in adopting them.…”
Section: Page 2 Of 34 Journal Of Enterprise Information Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…For many decades, Situation Awareness (SA) has been identified as one of the critical concepts to be considered (Yang et al, 2013). In this research Yang et al (2013) concluded that firefighters fear using technology as they are worried about the reliability of the existing systems and have procrastinated in adopting them.…”
Section: Page 2 Of 34 Journal Of Enterprise Information Managementmentioning
confidence: 99%
“…For many decades, Situation Awareness (SA) has been identified as one of the critical concepts to be considered (Yang et al, 2013). In this research Yang et al (2013) concluded that firefighters fear using technology as they are worried about the reliability of the existing systems and have procrastinated in adopting them. This clearly indicates that there is a significant lack of current literature outlining appropriate technology architectures for supporting unique and individual information requirements of different fire fighter job roles when responding to fire emergencies.…”
Section: Page 2 Of 34 Journal Of Enterprise Information Managementmentioning
confidence: 99%
“…Debido a que la información que disponen las víc-timas en una situación de evacuación es decisiva, y considerando la ubiquidad de dispositivos móviles, se plantea el desarrollo de aplicaciones que reúnan estos elementos [21,22]. El objetivo primordial que debe cumplir una aplicación de un teléfono móvil en una situación de emergencia es que las víctimas evacuen por la ruta más segura y corta en el menor tiempo posible [3].…”
Section: Desarrollo De Aplicaciones Móviles Para Situaciones De Emergunclassified
“…In remote areas, such as Africa and Asia, health care workers are often not able to gain access to patients quickly due to the large distances between the villages [68][69][70][71][72][73][74]. Once they do arrive on the scene, there is normally no record of the patient's condition due to a lack of monitoring and recording equipment.…”
Section: Digital First Respondermentioning
confidence: 99%